Diagnosa Tingkat Kolesterol Pada Remaja Menggunakan Metode Dempster Shafer - Pujiani Pujiani; Magdalena Simanjuntak; Siswan Syahputra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Teenagers are the age group from 10 years to before the age of 23 years. Adolescent health efforts aim to prepare adolescents to become healthy, intelligent, qualified and productive adults who play a role in maintaining, maintaining and improving their own health. In its grouping, cholesterol is included in the steroid group, which is a type of lipid that is not connected and is a fatty substance that has the property of not dissolving in the blood, which in the transportation process requires the help of protein to form particles which are usually called lipoproteins. Lipoprotein itself has several types, including LDL (low density lipoprotein), HDL (high density lipoprotein), triglycerides and total cholesterol. Dempster Shafer is the Dempster Shafer Method, also known as belief function theory. This method uses Belief, which is a measure of the strength of evidence in supporting a set of propositions. If the value is 0 (zero), it indicates that there is no evidence, and if the value is 1, it indicates that there is certainty. Based on the weight values ​​given by experts for each data on symptoms of cholesterol disease in adolescents, from the results of the analysis carried out in the previous chapter, the results of the diagnosis of cholesterol disease in adolescents were obtained, namely Low Density Lipoprotein (LDL) disease with a density value of 73.81%.